Antimicrobial resistance profiles of common mastitis pathogens on large Chinese dairy farms - Xiangbin Song; Yaxin Wang; Rina Bai; Xiaoyan Pei; Hongyan Xu; Kui Zhu; Congming Wu (JDS Communications, 2024)
The primary objective of this study was to determine the antimicrobial resistance (AMR) profile of common mastitis pathogens on large Chinese dairy farms. A total of 673 isolates, including Staphylococcus aureus (14.41%, 97/673), coagulase-negative staphylococci (CNS, 52.30%, 352/673), Streptococcus agalactiae (5.64%, 38/673), non-agalactiae streptococci (7.42%, 50/673), Acinetobacter spp. (7.72%, 52/673), Escherichia spp. (6.39%, 43/673), and Klebsiella spp. (6.09%, 41/673), were collected from 15 large Chinese dairy farms in 12 provinces. The AMR profiles were measured using a microdilution method. Our results showed that more than 75% of Staph. aureus (87/97) and CNS (291/352) were resistant to penicillin (PEN). More than 30% of Escherichia spp. (15/43) showed resistance to ampicillin (AMP). However, less than 10% CNS and non-agalactiae streptococci showed resistance to amoxicillin/clavulanate (AMC; 1/352; 0/50), cephalexin (LEX; 1/352; 0/50), ceftiofur (EFT; 10/352; 0/50), and rifaximin (RIX; 21/352; 2/50); less than 10% Staph. aureus showed resistance to AMC (1/97), oxacillin (OX; 3/97), LEX (1/97), EFT (2/97), and RIX (2/97); less than 10% Strep. agalactiae showed resistance to PEN (3/38), AMC (0/38), LEX (0/38), EFT (0/38), and RIX (0/38); and less than 10% Escherichia spp. showed resistance to AMC (1/43) and EFT (4/43). These results suggested that most mastitis pathogens were susceptible to most antimicrobials with exceptions of Staph. aureus tested against penicillin or ampicillin and CNS against penicillin or oxacillin. To control the AMR threat in Chinese dairy farms, a nationwide surveillance program for AMR of bovine mastitis pathogens is needed.